The viruses of Australia and the risk to tourists - Mackenzie, John; Speers, D.; Smith, D. (Elsevier Science, 2011)
Australia is a climatically diverse country varying from a tropical climate in the north to arid central desert and grassland regions, and to temperate climates in the south. There are many viral infections found in Australia that are common to developed countries worldwide, but this article will focus on those that pose a special risk for travellers to Australia, especially the mosquito-borne viruses. The commonest are the members of the alphavirus genus, particularly Ross River virus and Barmah Forest virus, which cause predominantly arthralgia with or without fever or rash. Less frequent but more serious illness is seen with the encephalitic flaviviruses, Murray Valley encephalitis virus, and the Kunjin strain of West Nile virus. In addition dengue occurs intermittently on the northern part of Queensland, and in recent years Japanese encephalitis virus has been found in the Torres Strait Islands and the tip of far north Queensland. Also of interest, but with a much lower risk, are the bat-borne viruses, Hendra virus and Australian bat lyssavirus, that have caused a small number of human infections. However, it is important to remember that most tourists pass through other countries in the Asia/Pacific region on their way to and from Australia and may therefore have acquired infections prior to or after leaving Australia.